Investigating the effects of Liushen Capsules (LS) on the metabolome of seasonal influenza: A randomized clinical trial - Ma, Qinhai; Chen, Ruihan; Zeng, Jing; Lei, Biao; Ye, Feng; Wu, Qihua; Li, Zhengtu; Zhan, Yangqing; Liu, Bin; Chen, Bojun; Yang, Zifeng (Frontiers in Pharmacology, 2022)
Background: Traditional Chinese Medicines (TCMs) are effective strategies for preventing influenza infection. Liushen Capsules can inhibit influenza virus proliferation, significantly mitigate virus-induced inflammation and improve acute lung injury in vitro or in vivo. However, the efficacy and safety in clinical trials, and the role of LS on regulating metabolites in patients are not well known. Materials and methods: A randomized, double-blind, placebo-controlled clinical trial was designed in this study. All participants were enrolled between December 2019 and November 2020. The efficacy and safety were assessed by primary efficacy endpoint and secondary endpoint. The serum samples were tested for metabolites using a non-targeted metabolomics ultra-performance liquid chromatography-tandem mass spectrometry (LC-MS). Results: 81 participants from The Second Affiliated Hospital of Guangzhou University of Chinese Medicine and the First Affiliated Hospital of Guangzhou Medical University were completed the full study. After 14 days of intervention, the area under the curve (AUC) of the total symptom scores in LS group was significantly smaller than that in Placebo group (P<0.001). Alleviation of sore throat, cough and nasal congestion in the LS group was significantly better than that in the placebo group. The time and number to alleviation of symptoms or complete alleviation of symptoms in LS group was significantly better than that in Placebo group. After 14 days of LS intervention, the levels of IL-1ra, Eotaxin, IFN-γ, IL-6, IL-10, IL-13, SCF and TRAIL in serum of participants with influenza infection were significantly decreased compared with Placebo group. It was observed significant differences in the serum metabolic profiles between start- and end- LS groups. Further correlation analysis showed a potential regulatory crosstalk between glycerophospholipids, sphingolipids fatty acyls and excessive inflammation and clinical symptoms. Importantly, it may be closely related to phospholipid, fatty acid, arachidonic acid and amyl-tRNA synthesis pathway metabolic pathways. Conclusions: The study showed a significant improvement in influenza-like symptom aspects and inflammatory response in patients treated with LS. Further analyze showed that LS could significantly correct the metabolic disorders in the serum metabolite profile of the patients. This provided new insights into the potential mechanism of LS for the treatment of influenza.